(a) (m₁+m₂)v=m₁v₁+m₂v₂
v₁(a)= {(m₁+m₂)v-m₂v₂}/m₁
(b) (m₁+m₂)v=m₁v₁-m₂v₂
v₁(b)= {(m₁+m₂)v+m₂v₂}/m₁
(c) (m₁+m₂)v=m₁v₁
v₁(c)= (m₁+m₂)v/m₁
v₁(b) > v₁(c)> v₁(a)
Question 2.
3 Consider a box that explodes into two pieces while moving with
Fig. 9-24
a constant positive velocity along an x axis. If one piece, with mass :
m1, ends up with positive velocity v1, then the second piece, with :
mass m2, could end up with (a) a positive velocity v2 (Fig. 9-25a), (b) :
a negative velocity v2 (Fig. 9-25b), or (c) zero velocity (Fig. 9-25c). Rank those three possible results for the second piece according to
:
the corresponding magnitude of v1, greatest first. v2v1v2 v1 v1
2 answers
a>b>c